Adolescents’ Neural Response to Social Reward and Real-World Emotional Closeness and Positive Affect - Flores, Luis E. (Cogn Affect Behav Neurosci, 2018)
Feeling emotionally close to others during social interactions is a ubiquitous and meaningful experience that can elicit positive affect. The present study integrates functional magnetic resonance imaging (fMRI) and ecological momentary assessment (EMA) to investigate whether neural response to social reward (1) is related to the experience of emotional closeness and (2) moderates the association between emotional closeness and positive affect during and following social interactions. In this study, 34 typically developing adolescents (ages 14–18) completed a social reward fMRI task, a monetary reward fMRI task, and a two-week EMA protocol regarding their social and affective experiences. Adolescents with greater right posterior superior temporal sulcus/temporoparietal junction (pSTS/TPJ) response to social reward reported greater mean momentary emotional closeness. Neural response to social reward in the right pSTS/TPJ moderated how strongly momentary emotional closeness was associated with both concurrent positive affect and future peak happiness, but in different ways. Although emotional closeness had a significant positive association with concurrent positive affect among adolescents at both high and low right pSTS/TPJ response based on a follow-up simple slopes test, this association was stronger for adolescents with low right pSTS/TPJ response. In contrast, emotional closeness had a significant positive association with future peak happiness among adolescents with high right pSTS/TPJ response but not among those with low right pSTS/TPJ response. These findings demonstrate the importance of neural response to social reward in key social processing regions for everyday experiences of emotional closeness and positive affect in the context of social interactions.